2021
DOI: 10.1192/j.eurpsy.2021.26
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an interaction between FXR1 and GSK3β polymorphisms on levels of Negative Symptoms of Schizophrenia and their response to antipsychotics

Abstract: Introduction: Genome Wide Association Studies (GWAS) have identified several genes associated with schizophrenia (SCZ) and exponentially increased knowledge on the genetic basis of the disease. Additionally, products of GWAS genes interact with neuronal factors coded by genes lacking association, such that this interaction may confer risk for specific phenotypes of this brain disorder. In this regard, FXR1 (Fragile-X mental-retardation-syndrome-related 1) gene has been GWAS associated with SCZ. FXR1 protein is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Targeting GSK3β or overexpressing FXR1 in the mouse prefrontal cortex led to behavioral effects similar to those of lithium and other mood stabilizers on anxiety-like behavioral dimensions in mice ( Latapy et al, 2012 ; Del'Guidice et al, 2015 ; Khlghatyan and Beaulieu, 2020 ). Furthermore, human SNPs affecting the expression of GSK3B and FXR1 genes in the human prefrontal cortex were shown to interact and affect emotional stability in controls, negative symptoms and antipsychotic drug responsiveness in schizophrenia, as well as symptom severity in bipolar disorder ( Del'Guidice et al, 2015 ; Bureau et al, 2017 ; Rampino et al, 2021 ).…”
Section: Direct Substrates Of Gsk3 Regulated By Lithiummentioning
confidence: 99%
“…Targeting GSK3β or overexpressing FXR1 in the mouse prefrontal cortex led to behavioral effects similar to those of lithium and other mood stabilizers on anxiety-like behavioral dimensions in mice ( Latapy et al, 2012 ; Del'Guidice et al, 2015 ; Khlghatyan and Beaulieu, 2020 ). Furthermore, human SNPs affecting the expression of GSK3B and FXR1 genes in the human prefrontal cortex were shown to interact and affect emotional stability in controls, negative symptoms and antipsychotic drug responsiveness in schizophrenia, as well as symptom severity in bipolar disorder ( Del'Guidice et al, 2015 ; Bureau et al, 2017 ; Rampino et al, 2021 ).…”
Section: Direct Substrates Of Gsk3 Regulated By Lithiummentioning
confidence: 99%
“…SNPs (signal nucleotides polymorphisms) of GSK-3β are described to be risk factors for schizophrenia. The synthesis of glycogen is regulated by two subunits of GSK-3 (α and β) [ 9 ]. AKT plays a role in cognition through its modulation of long-term potentiation, synaptic plasticity and, in consequence, working memory [ 10 ].…”
Section: Intracellular Signaling Pathwaysmentioning
confidence: 99%
“…Antipsychotics acting as DRD2 antagonists inhibit the assembly and activation of the complex of β-arrestin, PP2A and AKT. Next, the prevention of β-arrestin 2/PP2A recruitment leads to phosphorylation and the activation of AKT and, in consequence, the AKT signaling is not inhibited [ 9 , 13 ]. AKT is a convergent antipsychotic signaling mechanism.…”
Section: Intracellular Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that SNPs of the GSK3β gene can increase GSK3β promoter activity and alter transcriptional strength and splicing (Li M et al 2011; Kwok et al 2005). Other studies have indicated that GSK3β polymorphisms affect prefrontal cortical thickness, temporal lobe volume, and negative symptoms in schizophrenia (Blasi et al 2013;Benedetti et al 2010;Rampino et al 2021). This indicates that GSK3β polymorphism may be related to susceptibility to schizophrenia.…”
Section: Introductionmentioning
confidence: 98%